Seroprevalence of Cystic Echinococcosis in Yaks and Sheep During 2017 on the Qinghai–Tibet Plateau, China - Gao, Xing; Xire, Luosong; Zhang, Zhao; Quan, Chuxian; Zhou, Shimeng; Li, Kewei; Song, Rende; Zhao, Suonan; Kong, Xiangying; Naori, Cairang; Kulyar, Muhammad Fakhar-e-Alam; Bao, Yuhua; et al. (Frontiers in Veterinary Science, 2022)
Cystic echinococcosis (CE) is a livestock disease caused by a parasite known as Echinococcus granulosus. It is one of the primary cause for illness and poverty especially for herders on the Qinghai–Tibet plateau, China. Meanwhile, the Qinghai–Tibet plateau has been a key area for echinococcosis control in China. Here in current study, we determined the seroprevalence of E. granulosus in ruminants on this region. A total of 2,730 serum samples (1,638 samples from yaks and 1,092 samples from sheep) were collected on the plateau during the period of 2017. The samples were assayed for E. granulosus antibodies by commercial enzyme-linked immunosorbent assay kits. Our results exhibited a prevalence percentage of 52.2% in Tibetan yaks and 38.2% in Tibetan sheep. Moreover, there was more chance of being infected with E. granulosus infection in old animals due to more exposure to contaminated sources of infection. However, no significant difference was observed. Furthermore, we observed that the rainfall and presence of several lakes has increased the risk of CE infection in yaks and sheep in the Qinghai, Qinglong, and Baingoin areas. Hence, with this investigation, it was possible to determine the frequency and distribution of CE in yaks and Tibetan sheep on the Qinghai-Tibet plateau, that laying the groundwork for its prevention and management.